Dye degradation, antimicrobial activity, and molecular docking analysis of carbon sphere and graphene oxide–doped aluminum oxide - Zubair Arshad, Hafiz Muhammad; Imran, Muhammad; Haider, Ali; Shahzadi, Iram; Mustajab, Muhammad; Ul-Hamid, Anwar; Nabgan, Walid; Medina, Francisco; Aslam, Sadaf; Ikram, Muhammad (Frontiers in Environmental Science, 2023)
Dye degradation, antimicrobial activity, and molecular docking analysis of carbon sphere and graphene oxide doped aluminum oxide